Avaliação de curto prazo nos sintomas respiratórios em indivíduos expostos ao material particulado em ar ambiente - Squizzato, Rafaela (2017)
Studies that relate air pollution and health in medium-sized urban areas are scarce, especially in adults. In addition, there is no consensus in the literature regarding a safe level of airborne particulate matter, and therefore researches at these sites may contribute to a better understanding of the associations between health and pollution. The present study aims to evaluate the influence of short-term exposure caused by concentrations of particulate matter and black carbon in the respiratory symptoms of employees and students of two Higher Education Institutions (P1 and P2) located in Londrina with urban characteristics and emission sources different. Volunteers above 18 years of age were evaluated using the British Medical Research Council (BMRC) questionnaire on respiratory symptoms, adapted and validated. Indoor and outdoor measurements of concentrations of particulate matter were carried out at both institutions. The results show that the outdoor mean concentrations for MP2.5 were 7.1 μg m-3 for P1 and 4.8 μg m-3 for P2 in the summer, and 10.6 μg m-3 for P1 and 11 Μg m-3 for P2 in winter. The sites, although with different characteristics in the surroundings presented similar concentrations of particles, and between the seasons were not similar and superior in the winter. The indoor mean concentrations of PM1, PM2.5, PM4, PM10 and PTS for the summer were 5, 8, 13, 25 and 30 μg m-3 in P1 and 5, 8, 11, 21 and 26 μg m- 3 in P2, and for winter were 8, 11, 17, 36 and 43 μg m-3 in P1 and 9, 13, 18, 33 and 40 μg m-3 in P2, respectively. The number of particles for nP0.3, nP0.5, nP1, nP2.5 were 23599, 2050, 373, 117 particles L-1 and 24885, 1980, 294, 74 particles L-1 in summer and 52378, 641, 182 particles L-1 and 48297, 3514, 482, 116 particles L-1 in winter respectively in P1 and P2. There were no significant variations in black carbon concentrations between institutions and between seasons. Significant positive associations (p = 0.05) between the explanatory variables, period (RR 2.044, CI, 1.129-3.702), PM10 (RR, 1.031, CI, 1.016-1.110), PM2.5 (RR, 1.164, CI, 1.109-1.656) and nP2.5 (RR, 1.006, CI, 1.004-1.020) for the variable response (cough and phlegm) for the group of adult volunteers considered healthy. Thus, it was possible to verify that of the explanatory variables, the period and PM2.5 presented the highest risk factor for respiratory symptoms in healthy young/adults. In addition, an increase of 13% during the winter campaign on the prevalence of symptoms for the two sample sites even, in concentrations below the WHO limit.